Thinking about inequalities in physical activity as an emergent feature of complex systems - Sophie Marie Jones; Ana Porroche-Escudero; Katie Shearn; Ruth F. Hunter; Leandro Garcia (BMC, 2024)
Abstract Inequalities in physical activity are well documented, especially between socioeconomic groups. However, progress on reducing these inequalities is proving challenging. In this commentary, we argue that a complex system perspective is needed, specifically to reorient our thinking of inequalities in physical activity to be emergent features of complex systems. Operationalising this perspective involves acknowledging the multiple dynamic and non-linear interactions which take place between system parts and, over time aggregate to become macro patterns such as physical activity inequalities. We argue that this framing will enhance our understanding of the emergence of inequalities in physical activity and, therefore, provide interventions better suited to the subgroups of the population they are designed to help.